High yielding bread wheat genotype with potential to act as genetic barrier for rust spread in central India - and RAJBIR YADAV, JAGDISH KUMAR*, M. SIVASAMY, VINOD, G.P. SINGH (Indian Phytopathology, 2012)
The bread wheat genotype developed at IARI, regional station, Wellington and named as HW 5207 when evaluated under trials of All India Coordinated Wheat and Barley Improvement Project during 2007, 2008 and 2009 has recorded either significantly higher or at par mean grain yield (48.97q/ha) over all the checks and recently released varieties in central India. It has the yield potential of 51.3 q/ha. This genotype possesses gene Lr24 which stands resistant to all the Indian pathotypes of leaf rust as well as Sr2, a globally proven effective resistance gene which provides durable resistance to stem rust. Presence of Lr 24 and Sr2 in this genotype is validated with the help of suitable diagnostic markers. Development of rust resistant but high yielding wheat varieties like HW 5207 and their cultivation will add to diversification of the genetic basis of rust resistance and thereby put an impediment on build up of rust inoculum in central zone and its further spread to north western plain zone, the main wheat bowl of the country.